Skin transcriptome and physiological analyses reveal the metabolic and immune responses of yellow catfish (Pelteobagrus fulvidraco) to acute hypoxia - Wang, Man; Li, Bo; Wang, Jie; Xie, Songguang; Zhang, Lei (Aquaculture, 2022)
The skin of yellow catfish (Pelteobagrus fulvidraco) is scaleless, and therefore, represents the first line of defense against a wide variety of environmental stressors. However, the role of the skin in response to hypoxia is poorly understood. We aimed to examine the physiological and histological responses of the skin of yellow catfish to acute hypoxia and identify the genes regulating these responses. Healthy fish (weight: 12.75 ± 1.99 g) were randomly assigned to experimental tanks and subject hypoxic conditions (1.02 ± 0.08 mg/L) for 0, 6, 24, 48, and 96 h. The results showed that the physiological indices, including metabolic indices (LDH, SDH, GLU and LA) and immunological indices (LZM, IgM, and C3), showed similar trends in response to hypoxia. Histological examination revealed that the skins of the fish exposed to acute hypoxia had varying degrees of structural and tissue damage. Moreover, we identified 1638 differentially expressed genes (DEGs) from the skin tissues of the fish, among which 37 DEGs were common in all comparison groups. KEGG analysis showed that the DEGs were enriched in material metabolism (including carbohydrate and amino acid), energy metabolism, signal transduction, immune system, and apoptosis. We observed that the genes involved in carbohydrate, amino acid, and energy metabolism were significantly upregulated at 6, 24, and 48 h; however, genes related to the immune system and apoptosis were significantly downregulated at 6 and 24 h. Glycolysis/gluconeogenesis was the primary enriched pathways in response to hypoxia at 6 and 24 h. Hypoxia at 96 h was characterized by the overexpression of genes related to the immune system pathways and downregulation of genes related to the carbohydrate and energy metabolism pathways. The genes and signal pathways identified here provide new insights into the molecular mechanisms of the adaptation of yellow catfish to hypoxia. •We analyzed the skin transcriptome of Pelteobagrus fulvidraco under acute hypoxia.•Anaerobic and aerobic metabolism function in the response to acute hypoxia.•Acute hypoxia affects the immune system of the skin of P. fulvidraco.•The key turning point in the adaptation of P. fulvidraco to hypoxia occurs at 24 h.